Analisa Perilaku Stuktur Gedung Bertingkat yang Menggunakan Base-Isolation Systems - Tari Nurseptiani (Syntax Literate, 2023)
Indonesia is an earthquake-prone region, which can lead to collapse of buildings and casualties. Thus, the building must be designed to withstand earthquakes. The use of building protection systems against earthquakes other than shear walls is base isolation, according to base isolation is a protection system that reduces the effects of earthquakes by separating structures from the ground that moves during an earthquake, so as to reduce structural shifts and floor acceleration. In this study, the author developed a study from (Nurseptiani, 2020), namely by replacing the shear wall into base isolation to get a better structural response. The method used is a design analysis that aims to determine the behavior of the structure and the effectiveness of base isolation in multi-storey buildings, as well as using three-dimensional structures in the ETABS program. With the results of the reaserch, the period of the structure produced using base isolation increased by 5.565 seconds compared to fixed base and shear walls is 4.813 and 2.953 seconds. This also occurs in simple structures from 0.22 seconds to 1.017 seconds with base isolation. The resulting variety shape has a difference between the base isolation, fixed base and shear wall structures, this also happens with simple structures. The value of the base shear force generated in the base isolation structure experienced the greatest decrease of about 58.09% compared to the shear wall by only 25.88%. The deviation value between floors produced using base isolation has decreased and the value is the smallest. Based on the sample results of normal, shear and moment force values, base isolation has the smallest value, so from some of these points, it can be stated that base isolation is more effective than shear walls.